Peran metode pembelajaran praktik dalam meningkatkan minat kewirausahaan mahasiswa PJKR FIK UNNES dibidang olahraga - Tandiyo Rahayu; Billy Castyana; Dwi Gansar Santi Wijayanti; Endang Sri Hanani (Universitas PGRI Madiun, 2019)
Basically entrepreneurship is how to form the mindset, attitude, and behavior of people to become an entrepreneur. In addition, giving soft-skill to the students is also one way to equip students so they can have the character as entrepreneur. Soft-skill can be obtained through learning that prioritizes the approach of field practice, so that students can have real work experience. Segers (2004) stated that one of the key characteristics of effective learning and assessment models is to focus on high skills or competencies relevant to their future work. The aim of this study is to find out the role of field study for improving sport entrepreneurship’s interest on physical education students. This quantitative study was conducted using a 5-point likert survey method consist of three dependent variables and one independent variable with 115 respondents from Physical Education students. The data showed that the value of R is 0.662, this indicates that there is a moderate or strong relationship between field study (X) on entrepreneurship interest (Y). R square value of 0.439 could be interpreted that the field study can affect entrepreneurial interest of 43.9% while the remaining 56.1% is explained by other variables not examined in this study. Through the result of this study, we could see that field study has role to enhance the entrepreneurship’s interest, though there are other factors affect, such as the curriculum and educators.